Dynamic alterations in cerebral, celiac and renal flows resulting from ascending aorta, subclavian artery and femoral artery cannulations of extracorporeal devices. (October 2017) - Iscan, Sahin; Cakir, Habib; Eygi, Bortecin; Yurekli, Ismail; Donmez, Koksal; Ayvat, Pınar Unde; Pekel, Derya Sarıkaya; Kestelli, Mert
Introduction: The aim of this study was to assess the relationships among cardiac output, extracorporeal blood flow, cannulation site, right (RCa) and left carotid (LCa), celiac (Ca) and renal artery (Ra) flows during extracorporeal circulation. Methods: A mock circulatory circuit was assembled, based on a compliant anatomical aortic model. The ascending aorta, right subclavian and femoral artery cannulations were created and flow was provided by a centrifugal pump (Cp); cardiac output was provided by a roller pump (Rp). Five volume flow rates were tested. The Rp was set at 4 L/min with no Cp flow (R 4 -C 0 ) and the basic volume flow rates of the vessels were measured. The flow of the Cp was increased while the Rp flow was decreased for other measurements; R 3 -C 1, R 2 -C 2, R 1 -C 3 and R 0 -C 4 . Measurements were repeated for all cannulation sites. Results: The RCa flow rate at R 4 -C 0 was higher compared to the R 3 -C 1, R 2 -C 2, R 1 -C 3 and R 0 -C 4 RCa flows with subclavian cannulation. The RCa flow decreased as the Cp flow increased (p<0.05). The RCa flow with ascending aortic and femoral cannulation was higher compared to subclavian cannulation. Higher flows were obtained with subclavian cannulation in the LCa compared to the others (p<0.05). R 4 -C 0 Ca and Ra flows were higher compared to other Ca and Ra flows with femoral cannulation. Ca and Ra flows decreased as Cp flow increased. Flows of the Ca and Ra with ascending and subclavian cannulations were not lower compared to the R 4 -C 0 flow (p<0.05). Conclusion: This study shows that prolonged extracorporeal circulation may develop flow decrease and ischemia in cerebral and abdominal organs with both subclavian and femoral cannulations.